Bieda, Esteban. Platón y la voluntad: acción, razón y deseo en la obra platónica. 1°ed-Barcelona/ Buenos Aires: Miño y Dávila editores, 2021. 264 pp - López Nocera, Karen (Ideas y Valores, 2023)
The following is a review of Plato and the will: action, reason and desire in the platonic work, written by Esteban Bieda and published by the Argentine editorial house Miño y Dávila as part of the collection Studies of the Ancient Mediterranean PEFSCEA N°22. This book explores the concept of will in ancient times and seeks to answer the following question: was there already a concept of will in classical Greece or was the man conceived as a simple puppet whose strings were managed by fate and the gods?